2018
DOI: 10.4048/jbc.2018.21.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Benign Intraductal Papilloma without Atypia on Core Needle Biopsy Has a Low Rate of Upgrading to Malignancy after Excision

Abstract: PurposeThe management of benign intraductal papilloma (IDP) without atypia diagnosed on core needle biopsy (CNB) remains controversial. This study was performed to evaluate the rate of upgrading to malignancy or high-risk lesions after excision and to identify factors associated with upgrading using a large series of benign IDP cases without atypia.MethodsWe included patients who were diagnosed as having benign IDP without atypia on CNB and underwent surgical or vacuum-assisted excision between 2010 and 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
(61 reference statements)
3
35
2
3
Order By: Relevance
“…Therefore, caution is advised when recommending conservative management to that group of patients. On the other hand, we did not prove the predictive meaning of the accompanying clinical symptoms such as sanguine nipple discharge or multifocality of the lesions, which has been emphasized by Han et al [23]. Also, similarly to Rasmussen, we found no correlation between the volume of the lesions at imaging and the risk for BC underestimation, which has been suggested by Boufelli et al, and Yu et al [25,33].…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Therefore, caution is advised when recommending conservative management to that group of patients. On the other hand, we did not prove the predictive meaning of the accompanying clinical symptoms such as sanguine nipple discharge or multifocality of the lesions, which has been emphasized by Han et al [23]. Also, similarly to Rasmussen, we found no correlation between the volume of the lesions at imaging and the risk for BC underestimation, which has been suggested by Boufelli et al, and Yu et al [25,33].…”
Section: Discussioncontrasting
confidence: 75%
“…At present, medical advances and significant progress in the pathology-morphology diagnosis of the breasts, especially immunohistochemistry, allow for a more precise differentiation between various papillary growths [22]. Owing to that, the current underestimation of malignant BC at CNB ranges from 0.4 to 4% [23,24]. Also, due to the development of minimally invasive techniques, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, there have also been several studies reporting low upgrade rates, in which conservative management has been advocated. Han et al published a study of 511 cases of IDP without atypia of which 398 were treated with surgical excision. Only 0.8% were upgraded to a diagnosis of malignancy and 4.4% to a high‐risk lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al found that after excluding patients with a clinically concerning palpable mass, no patients were upgraded to malignancy. The presence of a symptom, concurrent contralateral breast cancer, and multifocal lesions was all predictive of upgrade to malignancy.…”
Section: Discussionmentioning
confidence: 99%